Perbedaan Daya Terima, Sisa dan Asupan Makanan pada Pasien dengan Menu Pilihan dan Menu Standar di RSUD Sunan Kalijaga Demak - Uyami, Uyami; Hendriyani, Heni; Wijaningsih, Wiwik (Poltekkes Kemenkes Semarang, 2014)
Background : Patient acceptance of food effect on the nutritional status of patients. The low patient acceptability of food this will adversely affect the nutritional status and patient outcome. Based on patient surveys conducted leftovers Nutritional Installation Sunan Kalijaga Hospitals Demakin 2012 on the standard menu there is an average of 26.6 % food waste.Objective :This study aims to determine the differences in acceptance of food, the rest of food and food intake in patients with selections menu and standards menu in Sunan Kalijaga Hospitals Demak.Method : This research includes comparative observational research is research that aims to see the difference between independent variables and the dependent veriabel related research. This study used a cross-sectional design with a sample of 15 groups and 15 groups of menu selections standard menuResults : The results showed the power received at the selections menu group has a very good majority of the categories, while the received power on the standard menu group has a majority in both categories. The rest of the food standard menu group average of 21.32%, while the remainder of the food selections menu group average values leftovers of 16.10%. Energy intake group average selections menu intake value of 2110.07, while the selections menu group protein intake mean intake value of 70.10. Energy intake standards menu group mean intake value of 1842.07, while protein intake standards menu group mean intake value of 63.77.Conclusion : There is no difference in the patient's acceptance of food on the selections menu and standards menu, there are differences in the rest of the food and energy and protein intake in patients with selections menu and standards menu.